2020
DOI: 10.3390/met10040514
|View full text |Cite
|
Sign up to set email alerts
|

A Tailored AlSiMg Alloy for Laser Powder Bed Fusion

Abstract: The majority of aluminum alloys used for laser powder bed fusion are based on the aluminum-silicon system, particularly alloys containing 7 to 12 wt.% silicon and less than 1 wt.% magnesium. Silicon has a beneficial influence on melt viscosity during casting and laser additive manufacturing and prevents the formation of cracks. This study focused on the development of a new AlSi3.5Mg2.5 alloy for laser powder bed fusion with a Mg-Si content above 1.85 wt.% Mg 2 Si, which is the solubility limit of the α-alumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 29 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…This more limited process window could be attributed to macroscopic cracking when the Al-15%Fe alloy powder is subjected to high laser powers and scan speeds (Figure 2a,c). Similarly, it is known to be difficult to process heattreatable wrought-type Al alloys (Al-Cu, Al-Mg-Si, and Al-Zn-Mg systems) using L-PBF, because those materials are highly sensitive to cracking during solidification [19][20][21][22][23][24][25][26][27][28][29]. The solidification cracks often propagate along the building direction (which likely coincides with the solidification direction) in a process called "hot cracking" [24,45], resulting in poor processability of high-strength Al alloys.…”
Section: Process Window Of Laser Parameters For Manufacturing Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…This more limited process window could be attributed to macroscopic cracking when the Al-15%Fe alloy powder is subjected to high laser powers and scan speeds (Figure 2a,c). Similarly, it is known to be difficult to process heattreatable wrought-type Al alloys (Al-Cu, Al-Mg-Si, and Al-Zn-Mg systems) using L-PBF, because those materials are highly sensitive to cracking during solidification [19][20][21][22][23][24][25][26][27][28][29]. The solidification cracks often propagate along the building direction (which likely coincides with the solidification direction) in a process called "hot cracking" [24,45], resulting in poor processability of high-strength Al alloys.…”
Section: Process Window Of Laser Parameters For Manufacturing Samplesmentioning
confidence: 99%
“…Optimization of the laser process parameters, in particular the laser power and scan speed, is required for the densification of Al-Fe alloy samples. In fact, the influence of L-PBF process parameters on porosity and cracking (L-PBF processability) had been extensively studied in the cases of Al-Si-based alloys [10,[16][17][18] and age-hardenable wrought-type alloys (the 2xxx, 6xxx, and 7xxx series) [19][20][21][22][23][24][25][26][27][28][29]. In comparison, similar research for the Al-Fe alloys remains limited [30], although a few reports considered application of the L-PBF process to the Al-Fe-based alloys [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…To date, aluminium alloys have attracted wide interest thanks to their excellent strength-to-weight ratio, but their considerable solidification shrinkage, tendency to oxidation, high laser reflectivity and the poor flowability of their powders make these alloys challenging to process by PBF-LBM [6][7][8]. Considering the non-printability by PBF-LBM of some of the traditional high-strength Al alloys, the challenge of creating new tailored compositions is still ongoing [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Churyumov et al [28] revealed that annealed SLM Al-Mg-Sc alloys exhibit excellent strength and ductility. Knoop et al [29] revealed that aging treatment parameters considerably affect the tensile strength of SLM Al-Si-Mg alloys.…”
Section: Introductionmentioning
confidence: 99%